Performance of SESDAQ 1987-1994 - Ng, Ping Hua (2014)
Entrepreneurship has been identified as one of the major driving forces behind the growth of the economy of many countries. Small and medium sized firms have been regarded as an important source of technological advancement and job creation. As a result, the Stock Exchange of Singapore Dealing and Automated Quotation System (SESDAQ) was set up to provide an avenue for these local enterprises with growth potential to raise equity funds for their expansion. The listing requirements are less stringent than the Main Board of Stock Exchange of Singapore Limited (SES). Fees charged by SES on SESDAQ are generally lower to encourage these young companies to seek listing.